The T-Bird – a new aircraft-towed instrument platform to measure aerosol properties and turbulence close to the surface: introduction to the aerosol measurement system - Z. Jurányi; C. Lüpkes; F. Stratmann; J. Hartmann; J. Schaefer; A.-M. Jörss; A. Schulz; B. Wetzel; D. Simon; E. Gebhard; M. Stöhr; P. Hofmann; et al. (Atmospheric Measurement Techniques, 2025)
This study introduces the T-Bird, a novel aircraft-towed platform developed to measure aerosol and turbulence properties close to the surface, particularly over sea ice and open water in the polar regions. The T-Bird, towed by the Alfred Wegener Institute's Polar aircraft, offers a unique capability to capture data from altitudes as low as 10 m while the aircraft operates at its lowest allowed operation altitude. This measurement platform allows for simultaneous data collection of aerosol, turbulence, and meteorological parameters across multiple vertical layers. The T-Bird is equipped with specialized aerosol instrumentation to assess particle number concentration, number size distribution, and absorption coefficient and to collect filter samples. It has been tested under Arctic conditions during the BACSAM (Boundary layer and Aerosol and Cloud Study in the Arctic, based on aircraft and T-Bird Measurements) campaign in October 2022. This paper provides technical details on the T-Bird's design, with special focus on the aerosol instrumentation and its performance during Arctic flights addressing measurement challenges in the lowermost atmosphere. The first measurements demonstrate its potential to enhance our understanding of aerosol dynamics and atmospheric boundary layer processes in remote environments.